The process of decentralizing public administration: Insights from new local governments in Nepal - Palikhe, Aruna; Maharjan, Nanda Kumar; Kyle, Jordan; Pradhan, Mamata; Adhikari, Madan (Wiley, 2025)
Federalism offers countries an opportunity to tailor public services to local needs, yet few studies examine the transition process itself. Nepal began its transition to federalism in 2015, decentralizing governance of key sectors. This study, based on in‐depth interviews with local leaders across five provinces, explores the challenges and opportunities of this shift within the agricultural sector. Findings highlight key administrative, fiscal, and political challenges, including staffing shortages, limited fiscal resources and autonomy, and coordination gaps between local and national policy planning. Despite these hurdles, decentralized policy planning has strengthened citizen participation, and respondents remain optimistic about federalism. We conclude with policy recommendations to support Nepal's federal transition and draw broader lessons for other countries undertaking similar reforms.